MODERN DEVELOPMENT TOOLS FOR THE SERVER SIDE OF WEBSITES - Семыкина, Дмитрий; Русаков, Алексей (SWorldJournal, 2021)
The article describes the main features of creating websites. The main goals and areas of application of client and server development are described. Modern technologies for server development are considered: C#, PHP, Python, Node.js, Java, as well as th